Effect of lamotrigine and environmental enrichment on spatial memory and other behavioral functions in rats - Nowakowska, Elzbieta; Czubak, Anna; Kus, Krzysztof; Metelska, Jana; Burda, Kinga; Nowakowska, Anna (Arzneimittelforschung, 2010)
Epileptic patients are at risk of experiencing cognitive deficits as a result of pharmacotherapy as well as etiology of epilepsy. Antiepileptic drugs increase inhibitory neurotransmission and reduce the responsiveness of neurons, and thereby may have a negative impact on memory. The enriched environment intensifies exploration of the new area behavior, which may have a positive impact on spatial memory in rats.Depression is among the most common affective disorders in epileptic patients, and using antidepressant drugs together with antiepileptics brings about the risk of interactions and intensifying side effects.The aim of the study was to assess the effects of lamotrigine (CAS 84057-84-1, LTG) (10 mg/kg i. p.), a new anticonvulsant with antidepressant and neuroprotective properties, for memory and other behavioral functions in rats in standard and enriched environments (EE). LTG improved spatial memory upon repeated administration of the drug both in the rats housed in standard conditions and those housed in EE. Exposure to an enriched environment significantly improved spatial learning. LTG showed antidepressant effect on the forced swimming test both in the rats housed in standard conditions and those housed in EE. In rats housed in EE the antidepressant effect occurred earlier. LTG had a low profile of adverse effects (activity meter, chimney test).
Keywords: Antiepileptics; CAS 84057-84-1; Enriched environment; Lamotrigine, antidepressant effect; Spatial memory